2023
DOI: 10.31545/intagr/156049
|View full text |Cite
|
Sign up to set email alerts
|

Impact damage to chickpea seeds during free fall

Abstract: The study aimed to determine the extent of the percentage of mechanical damage (seed breakage) to chickpea seeds due to the impact caused by free fall. Three independent variables were used in the test, namely: impact surface (concrete, metal, plywood and seed-on-seed), drop height (3, 6, 9, and 12 m) and seed moisture content (10, 15, 20, and 25% w.b.). The results showed that all three independent variables significantly influenced the percentage breakage of chickpea seeds. The seeds dropped onto concrete an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Loading grains into bins may cause mechanical damage as the grains are subjected to a free‐fall drop. The damage to the grains during free fall depends on various factors, such as drop height, grain conditions (grain size, volume, mass, temperature, and moisture content), and contact surface material (Delfan et al, 2022 ). Using vertical pipes, in silos and other grain handling or processing systems allows the grains to move at high speeds resulting in a high‐intensity impact on the grains when discharged, which may result in mechanical damage to the grain.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Loading grains into bins may cause mechanical damage as the grains are subjected to a free‐fall drop. The damage to the grains during free fall depends on various factors, such as drop height, grain conditions (grain size, volume, mass, temperature, and moisture content), and contact surface material (Delfan et al, 2022 ). Using vertical pipes, in silos and other grain handling or processing systems allows the grains to move at high speeds resulting in a high‐intensity impact on the grains when discharged, which may result in mechanical damage to the grain.…”
Section: Introductionmentioning
confidence: 99%
“…Various drop tests were performed with corn, chickpea, and soybean (Bartkowiak et al, 2019 ; Delfan et al, 2022 ; Shah et al, 2001 ). In a study on the improvement of grain quality by Bartkowiak et al ( 2019 ), they reported that corn grains with a moisture content of about 18% dropped using a cascade chute from 6‐m height showed four and five times less damage compared with the free fall.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations